An Unusual Association between Unilateral Intracranial Vessels Occlusion with Iron Deficiency Anaemia and Alpha-Thalassemia Trait: A Case Report - Yeong, Yeh Lee; Bhaskar, Shalini (Hindawi Publishing Corporation, 2011)
We report a 33-year-old Malay woman presented with acute left dense hemiparesis and an NIHSS score of 11/15. Computed tomography (CT) scan brain showed a massive right middle cerebral artery (MCA) territory infarct. The right internal carotid artery (ICA) and right proximal MCA were shown occluded from digital substraction angiography (DSA). Carotid dissection, carotid canal anomaly, and intercavernous communication were systematically ruled out. She had no risk factors for atherosclerosis. The connective tissue screening and thrombophilic markers were negative. However, she was anaemic on admission and subsequent investigations revealed that she had alpha-thalassemia and iron deficiency anaemia. The right ICA remained occluded from a repeat CT cerebral angiogram after one year, but otherwise she was neurologically stable. This case illustrates an unusual association between intracranial vessel occlusion with iron deficiency anaemia and alpha-thalassemia trait.